Impact of Physical Abuse on Juevinile Mental Health - Ishaq, Ayesha; Rasool, Atif; Majid, Saira; Mustafa, Usama; Asif, Fareeha (Pakistan Journal of Humanities and Social Sciences, 2025)
This study explores the multidimensional impact of physical abuse on juveniles, focusing on their mental health. Physical abuse characterized by acts of hitting, beating, or other forms of bodily harm can result in immediate physical injuries and long-term developmental complications. The study further investigates how such experiences contribute to the onset of mental health disorders including depression, anxiety, post-traumatic stress disorder (PTSD), and suicidal tendencies. In addition, behavioral manifestations such as aggression, withdrawal, delinquency, and academic decline are examined. These individual effects often translate into broader social challenges, influencing the juvenile’s role in society, interpersonal relationships, and potential for future success. This research aims to highlight the critical need for early detection, intervention, and policy reforms. By understanding the extensive consequences of physical abuse, the study underscores the importance of multidisciplinary efforts to protect vulnerable youth and support their reintegration into healthy societal roles.The sample was formed 60 juvenile and collected data from district jail and child protection bureau center.Pearson correlation analysis was used to study the relationship between physical abuse and mental health among the juveniles. This analysis showed strong but weak correlation estimate between physical abuse and mental health, observed to be r=.15, p=.263 based on the sample size of 60 respondents.